Communication, compliance, and concordance between physicians and patients with prescribed medications. - Hulka, B S (1976)
Forty-six practicing physicians and 357 patients with diabetes mellitus or congestive heart failure were the subjects for this study, which focuses on the impact of medication regimen and doctor-patient communication in affecting patient medication-taking behavior and physician awareness of these behaviors. Four types of medication errors were defined: omissions, commissions, scheduling misconceptions and scheduling non-compliance. The average error rates were 19 per cent, 19 per cent, 17 per cent and 3 per cent, respectively. The combined average error was 58 per cent; scheduline non-compliance on the part of the patient was a minor component. Specific aspects of the medication regimen were associated with increased errors: (1) the more drugs involved between the doctor-patient pair, the greater the errors of omission and commission; and (2) the greater the complexity of the scheduling, the greater the errors of commission and scheduling misconceptions. If the patient did not know the function of all his drugs, errors of commission and scheduling misconception increased. Neither characteristics of patients nor the severity of disease were influential in determining the extent of medication errors. For patients with congestive heart failure, good communication of instructions and information from physician to patient was associated with low levels of all types of errors.